1983
DOI: 10.1111/j.1471-4159.1983.tb08073.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Polyphosphoinositides in Developing Rat Brain

Abstract: Polyphosphoinositides in rat brain exist in two forms: the metabolically active form that is readily attacked by the polyphosphoinositide phosphohydrolases, and the inert form that is attacked by the enzymes at a slower rate. The two pools continue to increase even during the postweaning period, suggesting a role in glial as well as myelin development apart from their role in neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Among them, contribution by PA is a likely source. A rapid degradation of poly-PI after decapitation is known to occur in rats [Uma and Ramakrishnan, 1983;Huang and Sun, 19861. Thus, these results are in agreement with the contention that one of the initial biochemical changes occurring during ischemia is the stimulated breakdown of poly-PI by phospholipase C. This change is accompanied by massive Ca2+ influx and depolarization of the neuronal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, contribution by PA is a likely source. A rapid degradation of poly-PI after decapitation is known to occur in rats [Uma and Ramakrishnan, 1983;Huang and Sun, 19861. Thus, these results are in agreement with the contention that one of the initial biochemical changes occurring during ischemia is the stimulated breakdown of poly-PI by phospholipase C. This change is accompanied by massive Ca2+ influx and depolarization of the neuronal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The heads of the rats were frozen immediately. Following the procedure of Uma and Ramakrishnan (1983), the brain was isolated. Liver, lung, heart, kidney and brain were collected in precooled petri dishes and were blotted free of blood and tissue fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that cell phosphoinositides exist in metabolically distinct and therefore functionally different pools in various tissues. In brain tissue, the rapid postmortem hydrolysis of a portion of the polyphosphoinositides suggests the presence of metabolically active and inert pools of these lipids (Sheltaway and Dawson, 1969;Hauser et al, 1971;Uma and Ramakrishnan, 1983). The formation of phosphoinositides in tissues also involves different metabolic routes.…”
mentioning
confidence: 99%